Personality Traits Among Patients Who Underwent Cosmetic Rhinoplasty Surgery - Öztürk, Güncel (Cerrahpaşa Medical Journal, 2021)
Objective: Rhinoplasty is one of the most common cosmetic surgeries in esthetic plastic surgery. Regardless, there is no consensus about the associations between rhinoplasty and psychiatric condition in the literature. Although it is well known that personality traits affect emotions, ideas, and behaviors, no study has investigated personality traits in individuals who have undergone rhinoplasty. The current study aimed to compare the personality traits, self-esteem, and body perception of patients who underwent rhinoplasty with those of a control group of healthy volunteers. Methods: This study included 160 rhinoplasty patients and 100 healthy volunteers. The Basic Personality Traits Inventory (BPTI), the Self-Esteem Scale (RSES), and the Body Cathexis Scale (BCS) were applied to all the participants. Results: The scores for the BCS and the personality trait of extraversion were found to be higher in the rhinoplasty group than in the control group. Additionally, there were significantly positive correlations between the BCS score and the personality traits of extraversion and openness. There were also significantly positive correlations between the RSES score and the traits of neuroticism and negative valence. Conclusion: Patients who seek cosmetic rhinoplasty may have favorable personality traits such as extraversion. The present study is the first to demonstrate personality traits in cosmetic rhinoplasty patients. Further studies are needed to confirm these results. Cite this article as: Öztürk G. Personality traits among patients who underwent cosmetic rhinoplasty surgery. Cerrahpaşa Med J. 2021;45(2):129-134.